Retrospective epidemiological study of equine encephalitis in three departments of the eastern plains (Revista Sistemas de Producción Agroecológicos, 2021)
Eastern Equine Encephalitis (EEE) and Venezuelan Equine Encephalitis (EEV) are zoonotic infections of public health importance, because they can cause severe encephalitis in equids and humans due to mosquito bites and because of their high potential to cross borders; They are caused by viruses of the Togaviridae family, of the Alphavirus genus, some of which cause encephalitis in mammals and birds. They are enzootic in Venezuela and other parts of South America, with the VEE virus being responsible for major outbreaks of serious, often fatal disease in animals and humans. In Colombia there are areas with a higher risk of presentation, taking into account the circulation of the transmitting vectors and geographical conditions that favor their proliferation, which are located at altitudes lower than 1200 meters above sea level. The objective of this work was to determine the epidemiological behavior of equine encephalitis based on a descriptive-retrospective study in two departments of the Colombian Orinoquia region, during the years 2012-2018. The database was provided by the Instituto Colombiano Agropecuario - ICA and was analyzed using the Bortman method by endemic corridors. Finding that in the department of Casanare between the years 2012 to 2018 there were 62 outbreaks of EEE, with 91.9% of the cases in 2016; more frequently in the months of July, August and June, in the municipalities: Aguazul, Maní, Monterrey, Orocué, San Luis de Palenque, Tauramena, Trinidad and Yopal, without outbreaks in the control year 2019; of VEE there were two (2) outbreaks in the years 2012-2018; no cases in the control year 2019. In the department of Meta, there were eight (8) foci of EEE, the municipalities with the highest incidence being: Puerto Rico, Cumaral and Guamal. During this period in the study years, the months with the highest incidence were March, April and June. In the control year, an epidemic outbreak occurred during the months of February and March in the municipality of Puerto Rico, with a total of three (3) reported foci and 15 affected animals. There were two (2) outbreaks of VEE reported in 2016, in the months of January and July. The study yielded data that help to control Equine Encephalitis over time, being for the EEE the months of highest incidence July, August and September, probably due to the increase in environmental temperature in these months and therefore by the multiplication of vectors; while, for VEE, the months with the highest incidence were January, February, April and July.
Keywords: equine encephalitis; rainfall regime; vectors